Screening for unconventional pesticides in tropical fruits and vegetables from Hainan, China - Yijun Zhang; Li Xu; Chaozheng Wang; Xiaowei Liu; Wenguang Jiao; Yiwei Chen (PLoS ONE, 2026)
Hainan Province, a major tropical fruit and vegetable production region in China, faces potential threats to food safety and the ecological environment due to pesticide residue issues. However, the current monitoring system has notable limitations. Many unconventional pesticides (pesticides not included in Hainan’s routine pesticide residue monitoring program) are not systematically monitored, and residue limit standards for these substances are lacking, resulting in regulatory blind spots. In this study, the QuEChERS sample preparation method combined with GC-MS/MS was applied to systematically screen and evaluate 117 unconventional pesticides in 216 fruit and vegetable samples collected from the eastern, central, and western regions of Hainan. Results showed that target pesticides were detected in 23 samples (10.6% of the total sample size), with 18 of these samples (78.3% of the contaminated samples) containing pesticides not covered by the national pesticide residue limits. Peppers and Chinese cabbage exhibited the highest detection rates (39.4% and 21.2%, respectively). A total of 11 pesticide types were identified (9.40% of the screened types), with tetramethrin showing the highest detection frequency (39.1% of the contaminated samples) and isoprocarb exhibiting the highest concentration (1.775 mg/kg in celery). Furthermore, a correlation model was developed, indicating that geographical and climatic factors (32.6%), crop characteristics (28.3%), and pesticide properties (25.1%) are the main factors influencing pesticide residue levels. This study fills a critical data gap in unconventional pesticide residue monitoring in tropical agriculture of Hainan, providing a solid scientific basis for improving the regulatory system, updating residue limit standards, and ensuring the safety and quality of agricultural products.